Estimation of soil hydraulic and solute transport properties from field infiltration experiments (Research, Society and Development, 2021)
To model water flow and solute transport in soils, hydrodynamic and hydrodispersive parameters are required as input data in the mathematical models. This work aims to estimate the soil hydraulic and solute transport properties using a ponded axisymmetric infiltration experiment using a single-ring infiltrometer along with a conservative tracer (Cl-) in the field. Single ring infiltration experiments were accomplished on an Oxisol in Areia in the state of Paraíba, Brazil (6o 58' S, 35o 41' W, and 645 m), in a 50 x 50 m grid (16 points). The unsaturated hydraulic conductivity (K) and the sorptivity (S) were estimated for short or long time analysis of cumulative three-dimensional infiltration. The single tracer technique was used to calculate mobile water fraction (Ф) by measuring the solute concentration underneath the ring infiltrometer at the end of the infiltration. Two solute transfer numerical models based on the mobile-immobile water concept were used. The mobile water fraction (Ф), the dispersion coefficient (D), and the mass transfer coefficient (a) between mobile and immobile were estimated from both the measured infiltration depth and the Cl- concentration profile underneath the infiltrometer. The classical convection-dispersion (CD) and the mobile-immobile (MIM) models showed a good agreement between calculated and experimental values. However, the lowest standard errors to the fitted parameters were obtained by the CD model.